Towards Bali's Energy Independence: Potential and Challenges in Developing Renewable Energy Power Plants - Putu Gede Agus Krisna Yogantara; Freygieon Ogiek Rizal Sukma; Hangga Novian Adi Putra (Jurnal Energi Baru dan Terbarukan, 2026)
The use of electricity on the island of Bali currently still relies heavily on supply from the island of Java, with most of the electricity coming from fossil-based power plants. In reality, Bali has quite abundant potential for new and renewable energy (NRE) both on land and at sea. This research aims to comprehensively review the technical potential of various NRE sources in Bali along with the challenges of their implementation, as well as to formulate scenarios for the development of integrated power plants toward energy independence. Based on a synthesis of recent literature studies and policy data, Bali has a technical NRE potential of up to 22 GW, with solar power being the most strategic short term option through the development of rooftop solar power plants of up to 2.7 GW by 2034. However, this review also identifies that in reality, achieving this potential is still far from the expected target, as the distribution of new NRE use only reached 1.48% in 2023. The critical challenges identified include socio-cultural conflicts such as the geothermal project in Bedugul, past failures of communal wind projects, inconsistent policies that still prioritize gas-fired power plants, as well as regulatory barriers that limit private sector investment. As a solution, a scenario is proposed for the development of integrated power plants in five strategic locations in Bali, along with policy recommendations to accelerate the energy transition, including reforms of electricity trade regulations, incentives for renewable energy investments, and the resolution of socio-cultural conflicts through a participatory multi-stakeholder approach.